Influence of Pilates training on muscular strength and flexibility in dancers - Tânia Patrícia Amorim; Filipa Manuel Sousa; José Augusto Rodrigues dos Santos (Universidade Estadual Paulista (UNESP), 2011)
The purpose of the present study was to assess the effects of a Pilates training program on muscular strength and flexibility in dance students. Fifteen dance students were divided into 2 groups: experimental (n=7) and control (n=8). Both were assessed in beginning and in the end of the study. Muscular strength was assessed measuring the time supported in the technical skills penché and developpé. To asses flexibility, it was measured the angle between limbs in the technical skills arabesque, developpé and cambré. After the first moment of evaluation, the experimental group performed a Mat-Based Pilates Exercise during 11 weeks. The statistic analyses (two-way analysis of variance - ANOVA 2x2) showed significant differences (p ≤ 0,05) in muscular strength and flexibility measurements between groups after the training program. It was concluded that Pilates training has a positive effect on muscular strength and flexibility in dance students.